Use of monoclonal antibodies to analyse the expression of a multi-tubulin family. - Birkett, C; Foster, K; Johnson, L; Gull, K (1985)
We have used a panel of monoclonal antibodies in a study of the expression of multiple tubulins in Physarum polycephalum. Three anti-beta-tubulin monoclonal antibodies, DM1B, DM3B3 and KMX-1 all reacted with the beta 1-tubulin isotypes expressed in both myxamoebae and plasmodia. However, these antibodies showed a spectrum of reduced reactivity with the plasmodial beta 2-tubulin isotype - the competence of recognition of this isotype was graded DM1B greater than KMX-1 greater than DM3B3. The anti-alpha-tubulin monoclonal antibody, YOL 1/34 defined the full complement of Physarum alpha-tubulin isotypes, whilst the anti-alpha-tubulin monoclonal antibody, KMP-1 showed a remarkably high degree of isotype specificity. KMP-1 recognises all of the myxamoebal alpha 1-tubulin isotypes but only recognises 3 out of the 4 alpha 1-tubulin isotypes expressed in the plasmodium (which normally focus in the same 2D gel spot). KMP-1 does not recognise the plasmodial specific alpha 2-tubulin isotype. This monoclonal antibody reveals a new level of complexity amongst the tubulin isotypes expressed in Physarum and suggests that monoclonal antibodies are valuable probes for individual members of multi-tubulin families.